Constructivist perspective on Japan’s Foreign Aid Loans; In Case Jakarta Wastewater Infrastructure - Lalu Radi Myarta; Tulus Warsito; Nadhif Fadhlan Musyaffa; Hasri Ainun Hakiem (Jurnal Hubungan Internasional, 2023)
This study discusses Japan foreign aid in Indonesia which focus on wastewater treatment (IPAL) in Jakarta. The author is interested to conduct the research on answering the question of what is the real interest behind the Japanese aid. In describing the data on Japanese loan, the author used the qualitative method and in doing further analysis, this study used a constructivist approach of identity typology. The author believes that the ongoing of foreign aid shape identity of the donor country through bilateral or multilateral interaction. In which this study found that Japanese aid is motivated by identity interests, which encompasses role identity as environmentalist and collective identity in the foreign aid practice. By fulfilling this interest, Japan is considered capable of complying with or following international norms, where rich countries have to share their resources to developing countries so that it has an impact on increasing Japan's identity and reputation on a global scale. The logic of appropriateness valued Japan’s loan was in line with the international norm. As collective identity of both, Indonesia often hit by disaster as same as Japan’s. Therefore, Japan embedded its identity as a role model for Indonesia by installing resilient infrastructure of wastewater treatment in Jakarta.